2015
DOI: 10.1002/pts.2127
|View full text |Cite
|
Sign up to set email alerts
|

Packaging's Role in Minimizing Food Loss and Waste Across the Supply Chain

Abstract: This paper presents the results of Australian research that explored the role of packaging in minimizing food waste in the supply chain. The economic, social and environmental costs of food waste have been well documented elsewhere. This research contributes to the debate by identifying opportunities to reduce or recover food loss and waste through improved packaging.In the fresh produce sector, e.g. waste can be reduced through the use of packaging that improves product protection, ventilation and temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
200
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(208 citation statements)
references
References 31 publications
3
200
0
5
Order By: Relevance
“…Beyond the traditional and basic view of packaging as a means of protecting products (Williams et al, 2008;Verghese et al, 2015), over the last few years, new design requirements have been added for packaging: on the one hand, to improve the differentiation capacity of the product (commercial function), and on the other, to improve the efficiency of the product at a logistic and production level (logistic function).…”
Section: Developing a "Packaging Logistics" Approachmentioning
confidence: 99%
“…Beyond the traditional and basic view of packaging as a means of protecting products (Williams et al, 2008;Verghese et al, 2015), over the last few years, new design requirements have been added for packaging: on the one hand, to improve the differentiation capacity of the product (commercial function), and on the other, to improve the efficiency of the product at a logistic and production level (logistic function).…”
Section: Developing a "Packaging Logistics" Approachmentioning
confidence: 99%
“…European Council (1994), and research (Beitzen-Heineke et al 2017;Tencati et al 2016;Tua et al 2017) that focus on packaging prevention. On the other hand, in the recent debate about food waste, the protective function Responsible editor: Hans-Jürgen Garvens * Katrin Molina-Besch katrin.molina-besch@plog.lth.se 1 of packaging has been highlighted as an important environmental benefit (Bertoluci et al 2014;Verghese et al 2015;Williams et al 2008). Several studies have shown that the indirect environmental impact of packaging is of greater relative importance in many food supply chains than its direct environmental impact (Büsser and Jungbluth 2009;Silvenius et al 2014;Wikström and Williams 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The indirect environmental impact of packaging is the impact caused by the influence that packaging has on the food product's life cycle. It includes the influence on the amount of food waste and the possibilities of recovering food waste (Verghese et al 2015), the influence on transport efficiency in the food supply chain ) and the influence on consumers behaviour affecting food transport, storage and preparation in households (Zampori and Dotelli 2014). Life cycle assessment (LCA) appears to be a useful method for performing a complete analysis of the environmental impact of food packaging systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations